The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.15666/aeer/1606_75757583
|View full text |Cite
|
Sign up to set email alerts
|

FOLIAR APPLICATION OF GLYCINEBETAINE (GB) ALLEVIATES THE CADMIUM (Cd) TOXICITY IN SPINACH THROUGH REDUCING Cd UPTAKE AND IMPROVING THE ACTIVITY OF ANTI-OXIDANT SYSTEM

Abstract: Aamer et al.: Foliar application of glycinebetaine (GB) alleviates the cadmium toxicity in spinach through reducing Cd uptake and improving the activity of anti-oxidant system -7575 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…All these resulted in an increased tolerance capacity of the plants. Glycine betaine further increased the activity of the antioxidant system (Figs 4-6) which in turn prevents plants from oxidative damages caused by ROS generated due to stressed conditions that might also be the reason for the enhanced amelioration process in sorghum plants [68][69][70][71]. Aamer et al [69] demonstrated similar effects on GB application in spinach under Cd toxicity, as were observed during the present investigation.…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…All these resulted in an increased tolerance capacity of the plants. Glycine betaine further increased the activity of the antioxidant system (Figs 4-6) which in turn prevents plants from oxidative damages caused by ROS generated due to stressed conditions that might also be the reason for the enhanced amelioration process in sorghum plants [68][69][70][71]. Aamer et al [69] demonstrated similar effects on GB application in spinach under Cd toxicity, as were observed during the present investigation.…”
Section: Plos Onesupporting
confidence: 85%
“…Glycine betaine further increased the activity of the antioxidant system (Figs 4-6) which in turn prevents plants from oxidative damages caused by ROS generated due to stressed conditions that might also be the reason for the enhanced amelioration process in sorghum plants [68][69][70][71]. Aamer et al [69] demonstrated similar effects on GB application in spinach under Cd toxicity, as were observed during the present investigation. Bharwana et al [72] also obtained similar results that GB application enhances the amelioration behaviour of cotton plants grown under lead (Pb) toxicity.…”
Section: Plos Onesupporting
confidence: 85%
“…Toxic metals retain in soil and affect the soil microbes and plant growth and subsequently transferred into plants and impact the human health by entering the food chain [5]. Moreover, they also induced serious alteration in plants ranging from reduction in growth to subsequent mortality [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium stress induces serious impacts on the physiological, biochemical and morphological processes of plants [11]. It also disturbs the cell redox status and causes damage to major molecules through overproduction of ROS by inhibiting the activities of anti-oxidant enzymes [6,12]. Cadmium stress also disrupts membrane permeability, stomatal movements, photosynthesis, water relations and plant mineral nutrition [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This increase in grain yield might be resulted due to reduction in Cr uptake on GB and AMF application which in turn decreased stress level by maintaining proper stomatal conductance, chloroplast ultrastructure, RuBisCo activity, photosynthetic capacity and proper nutrient uptake [60]. Glycine betaine increased the antioxidant systems activity which in turn prevents plants from oxidative damages caused by ROS generated due to stressed conditions that might resulted in enhanced grain yield [61][62][63] demonstrated similar effects on AMF inoculation in sun ower under Cd toxicity, as were observed during present investigation. Similarly, GB application increased the growth and yield in rice plants under Cd toxicity [41].…”
Section: Discussionmentioning
confidence: 99%